1999
DOI: 10.1295/polymj.31.1211
|View full text |Cite
|
Sign up to set email alerts
|

Segregation Processes in Segmented Polyurethaneurea Solutions Observed by Fluorescence Depolarization

Abstract: ABSTRACT:The onset of a segregation process in segmented polyurethaneurea (SPUU) solutions was studied by fluorescence spectroscopy using free fluorescein as a probe. For SPUUs with a given molecular weight and a constant ratio of the hard to soft segments, the time-resolved fluorescence measurements reveal the environmental inhomogeneity on the excited lifetime of fluorescein. It is shown in this work that the critical concentration for the segregation process detected by fluorescence spectroscopy through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Phase separation has been studied using a number of techniques, most notably small‐angle X‐ray scattering (SAXS)1,7,9–20 and differential scanning calorimetry (DSC) 16,20–27…”
Section: Introductionmentioning
confidence: 99%
“…Phase separation has been studied using a number of techniques, most notably small‐angle X‐ray scattering (SAXS)1,7,9–20 and differential scanning calorimetry (DSC) 16,20–27…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that the SPUU samples microphaseseparate at polymer concentrations as low as 15 wt %. 21 In the past, fundamental researches on structures in SPUs and SPUUs have been directed to reveal crystalline structures of hard segments and higher order structures of hard-segment domains, such as spherulites, as well as microdomain structures. [1][2][3][4][5][6][7][8][9][10][11][13][14][15][16][17][18][19][20] The hard segments of MDI-butanediol (BDO) were reported to give some diffraction arcs in a wide-angle X-ray diffraction pattern.…”
Section: Introductionmentioning
confidence: 99%